The Effectiveness of Think Aloud Strategy to Improve Students' Writing Simple Present Tense on Descriptive Text - Dian Rismayanti (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2019)
This research aims to improve student grades and student activity in learning simple present tense in the descriptive text by using think aloud strategy and motivate students to more quickly and easily learn simple present tense in the descriptive text. SMPN 1 MUNDU Cirebon was chosen as the place for this research. There are 2 classes namely control class and experimental class consisting of 20 students in each class who participated in this study. Data were collected using Triangulation techniques. Triangulation can be defined as the use of two or more data collection methods in this study. The purpose of triangulation is to increase the credibility and validity of findings. In addition, the authors collected data using Pre-test, post-test and questionnaire. This study found that in the Control class the high score was 26%, Medium 42% and the low score 32% and in this Experimental class the researcher used think aloud strategy and produced the high score of 35%, Medium 44% and the Low score 21%. In these values it can be simplified that applying think aloud strategy to simple present tense learning in the descriptive text can be understood and accepted by students. So the results of the learning value that is quite satisfying. Keywords: Think aloud strategy: students writing: simple present tense: descriptive text